2019
DOI: 10.1177/2474126419836067
|View full text |Cite
|
Sign up to set email alerts
|

Automated Segmentation Measurements of the Outer Nuclear Layer in Determining Cases of Hydroxychloroquine Toxicity: A Retrospective Study

Abstract: The purpose of this article is to investigate automated segmentation measurements of the outer nuclear layer to differentiate patients with hydroxychloroquine toxicity from healthy individuals. Methods: A 5-year retrospective, casecontrolled, interventional study of hydroxychloroquine toxicity patients was conducted. Measurements of the outer nuclear layer were obtained with use of commercially available segmentation software and compared with controls. Results: Seven participants (13 eyes) with toxicity and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Prior studies have sought to use either commercially available or customized software to assess parafoveal loss of outer versus inner retinal layers for hydroxychloroquine retinal toxicity, which has a well-established and discernable predilection for parafoveal OCT changes. [28][29][30][31] Other work has suggested that for hydroxychloroquine toxicity the outer nuclear layer (ONL) thinning may precede parafoveal ellipsoid disruption, or continue after cessation. 32,33 As such, perhaps subtle thinning of the ONL as measured by automated segmentation in CLN2 disease may precede more advanced photoreceptor outer segment degeneration and thus serve as a sensitive biomarker for disease onset, progression, and response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have sought to use either commercially available or customized software to assess parafoveal loss of outer versus inner retinal layers for hydroxychloroquine retinal toxicity, which has a well-established and discernable predilection for parafoveal OCT changes. [28][29][30][31] Other work has suggested that for hydroxychloroquine toxicity the outer nuclear layer (ONL) thinning may precede parafoveal ellipsoid disruption, or continue after cessation. 32,33 As such, perhaps subtle thinning of the ONL as measured by automated segmentation in CLN2 disease may precede more advanced photoreceptor outer segment degeneration and thus serve as a sensitive biomarker for disease onset, progression, and response to treatment.…”
Section: Introductionmentioning
confidence: 99%